Penerapan Permainan Bola untuk Meningkatkan Kemampuan Mengenalkan Warna pada Anak Usia 4-5 Tahun di RA As-Sunniyah Desa Penawungan Kecamatan Ranuyoso Kabupaten Lumajang - Holifah Holifah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Color recognition is one aspect that needs to be developed for young children so that children can easily recognize their surroundings. The role of teachers for young children in kindergarten education is highly expected to help develop the ability to recognize colors according to the characteristics of early childhood, such as by learning through playing, namely ball games to recognize colors. The aim of this research is to describe the results of ball games in introducing colors to children aged 4-5 years at RA As Sunniyah Lumajang. The research used classroom action research with a sample size of 22 children. This PTK is carried out in two learning cycles. Based on the results of the two cycles, it can be seen that the development of color recognition in children aged 4-5 years at RA As Sunniyah Lumajang can improve and develop well through playing ball. The suggestions that researchers can convey are as follows: for teachers when delivering material, it should be delivered in a playful manner so that learning is enjoyable; for schools to improve the quality of education by using creative and interesting learning methods; for future researchers it is hoped that they can find new methods to introduce colors to early childhood